Metaphysics of Finance Economy: Of its Radicalization as the Method of Revoking Real Economy - Kolozova, Katerina (Identities: Journal for Politics, Gender and Culture, 2015)
My claim here is that there is no exit from metaphysics. We are metaphysical creatures inasmuch as we are material, the latter always already inviting the former. However, an exit from the disciplining and hallucinatory grasp of philosophical metaphysics or from philosophy is possible, as both Marx and Laruelle have shown. The effects of such exit will not only be intellectual or academic, but also social. Philosophical decisionism in an absolute form is the essence of capitalist economy and politics, and I will try to demonstrate this further on. Nonetheless, the ideas of political system or the possibilities of thinkable political horizons remain or become ever more detached from the economic logic of the liberal, pseudo-materialistic and individualist philosophy of exploitation through alienation called capitalism. Author(s): Katerina Kolozova Title (English): Metaphysics of Finance Economy: Of its Radicalization as the Method of Revoking Real Economy Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 11, No. 1 (Summer 2015) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 19-31 Page Count: 12 Citation (English): Katerina Kolozova, “Metaphysics of Finance Economy: Of its Radicalization as the Method of Revoking Real Economy,” Identities: Journal for Politics, Gender and Culture, Vol. 11, No. 1 (Summer 2015): 19-31.